Characteristics of the synoptic conditions of summer extreme heavy precipitation in the Yellow River Basin - Jun CHANG; Jun WANG; Lu WU; Hengbin SHI; Leilei ZHU (暴雨灾害, 2022)
Extreme heavy precipitation in the Yellow River basin mainly occurred between June and August in summer. It is of great significance for improving climate prediction and preventing and reducing disaster events to study the characteristics of synoptic conditions of extreme heavy precipitation in summer in this basin. Using the daily precipitation data in summer at the 247 ground-based meteorological stations in the Yellow River basin from 1961 to 2017, we first analyze the distribution characteristics of regional extreme heavy precipitation events in this basin. Second,according to the dominant circulation systems at 500 hPa,the typical circulation patterns affecting regional extreme heavy precipitation in summer in this basin are classified into the blocking type,the low-trough type,and the typhoon-peripheral type. The characteristics of extreme heavy precipitation,water vapor transport and evolution,and circulation under the blocking type and low-trough type of synoptic conditions before the events are analyzed. The results show that (1) the thresholds of extreme heavy precipitation in summer in the Yellow River basin gradually increase from the east to the west and from the north to the south during past 57 years. The frequency of extreme heavy precipitation in the upstream area is higher than that in other areas. (2) The distribution characteristics of zonal wind anomalies at 200 hPa are similar for the blocking-type and low-trough type synoptic conditions,whose anomalies show a "- + -" pattern in the range of 20°-55°N from the north to the south. Their circulation patterns at 500 hPa vary greatly,with the low-trough type dominated by the zonal circulation and the blocking type dominated by the meridional circulation in the mid- and high- latitudes of Eurasia. The former has many small troughs and ridges in the range of 30°-65°N,while the latter is controlled by positive geopotential height anomalies in the low latitudes. (3) The water vapor of blocking-type synoptic condition mainly comes from the Indian Ocean and the Pacific Ocean,while that of the low-trough type mainly comes from the Pacific Ocean and the South China Sea. (4) The blocking high that causes extreme heavy precipitation mainly develops locally,and the signal of its development can be captured 1-2 weeks before its occurrence. The trough that causes extreme heavy precipitation mainly moves,and its initial signal and strong signal appear about 7 d and 2-3 d before the occurrence of extreme heavy precipitation,respectively.